Phase separation in biology and disease—a symposium report. Issue 1 (14th June 2019) - Cable, Jennifer; Brangwynne, Clifford; Seydoux, Geraldine; Cowburn, David; Pappu, Rohit V.; Castañeda, Carlos A.; Berchowitz, Luke E.; Chen, Zhijuan; Jonikas, Martin; Dernburg, Abby; Mittag, Tanja; Fawzi, Nicolas L.
Abstract: Phase separation of multivalent protein and RNA molecules enables cells the formation of reversible nonstoichiometric, membraneless assemblies. These assemblies, referred to as biomolecular condensates, help with the spatial organization and compartmentalization of cellular matter. Each biomolecular condensate is defined by a distinct macromolecular composition. Distinct condensates have distinct preferential locations within cells, and they are associated with distinct biological functions, including DNA replication, RNA metabolism, signal transduction, synaptic transmission, and stress response. Several proteins found in biomolecular condensates have also been implicated in disease, including Huntington's disease, amyotrophic lateral sclerosis, and several types of cancer. Disease‐associated mutations in these proteins have been found to affect the material properties of condensates as well as the driving forces for phase separation. Understanding the intrinsic and extrinsic forces driving the formation and dissolution of biomolecular condensates via spontaneous and driven phase separation is an important step in understanding the processes associated with biological regulation in health and disease. Abstract : Phase separation of multivalent protein and RNA molecules enables cells the formation of reversible nonstoichiometric, membraneless assemblies. These assemblies, referred to as biomolecular condensates, help with the spatial organization and compartmentalization of cellular matter, but they are also associated with disease, such as Alzheimer's disease. This symposium report summarizes current research.